(untitled) (Salam International Academic Journal, 2025)
This paper presents the findings and discussion on the factors responsible for the emigration of female Afghan academics and scholars from Afghanistan. The review of literature had highlighted a significant lacuna in engagement and voice of migrant female Afghan academics. Thereby, the research undertaken through an exploratory interpretative-narrative case study approach uncovered three emergent themes leading to the identification of a single major factor influencing their decision. The interview schedule, as an ensuing narrative, uncovered the loss of individual liberty; the paucity in criticality in academic thought-practice (praxis) and the ‘lack of belonging both within academia and society’ as underlying factors, which the study classifies as emergent themes to formulate and identify the driving force and motivation for emigration, the major finding of the study, which is encapsulated in the notion of an ‘enforced disengagement’.